Reciprocal Effects between Reading Achievement and Intrinsic and Extrinsic Reading Motivation - Hebbecker, Karin; Förster, Natalie; Souvignier, Elmar (Scientific studies of reading, 2019)
Research on reading achievement and reading motivation has rarely addressed the question if and how they affect each other over time. In our study, we investigate the reciprocal effects between reading achievement and both intrinsic and extrinsic reading motivation during elementary school. We measured reading achievement and intrinsic and extrinsic reading motivation in 966 students at 3 points of measurement during 3rd and 4th grade. Consistent with previous research, cross-lagged panel analyses revealed positive reciprocal effects between reading achievement and intrinsic reading motivation. Effects of reading achievement on intrinsic reading motivation were found during Grades 3 and 4, whereas effects of intrinsic motivation were limited to Grade 3. No reciprocal effects between reading achievement and extrinsic reading motivation were found. We discuss the implications of our results for daily teaching practices and effective reading instruction.